Factors influencing domestic energy choice of rural households in Ogun State, Nigeria (2012)
Choices of domestic energy that are made by rural households are able to influence environmental conservation and sustainable development. This study determined the factors influencing choice of energy by rural households. Data were collected from randomly sampled households. Analysis was done with descriptive statistics and Logit regression. Result showed that the largest proportion of the respondents used kerosene oil for cooking and lighting. Logit regression results showed that there was gender influence in fuel wood choice. Also, illiterate household heads had higher likelihood of choosing charcoal. Choices of kerosene oil and electricity were influenced by proximity. It was recommended that efforts to address energy problem in rural areas should take cognizance of ensuring availability and affordability of cleaner energy sources, among others.